Influence of maternal and socioeconomic factors on breast milk fatty acid composition in urban, low‐income families. Issue 4 (15th February 2017) - Nayak, Uma; Kanungo, Suman; Zhang, Dadong; Ross Colgate, E.; Carmolli, Marya P.; Dey, Ayan; Alam, Masud; Manna, Byomkesh; Nandy, Ranjan Kumar; Kim, Deok Ryun; Paul, Dilip Kumar; Choudhury, Saugato; et al.
Abstract: The lipid composition of breast milk may have a significant impact on early infant growth and cognitive development. Comprehensive breast milk data is lacking from low‐income populations in the Indian subcontinent impeding assessment of deficiencies and limiting development of maternal nutritional interventions. A single breast milk specimen was collected within 6 weeks postpartum from two low‐income maternal cohorts of exclusively breastfed infants, from Dhaka, Bangladesh ( n = 683) and Kolkata, India ( n = 372) and assayed for percentage composition of 26 fatty acids. Mature milk (>15 days) in Dhaka ( n = 99) compared to Kolkata ( n = 372) was higher in total saturated fatty acid (SFA; mean 48% vs. 44%) and disproportionately lower in ω3‐polyunsaturated fatty acid (PUFA), hence the ω6‐ and ω3‐PUFA ratio in Dhaka were almost double the value in Kolkata. In both sites, after adjusting for days of lactation, increased maternal education was associated with decreased SFA and PUFA, and increasing birth order or total pregnancies was associated with decreasing ω6‐PUFA or ω3‐PUFA by a factor of 0.95 for each birth and pregnancy. In Dhaka, household prosperity was associated with decreased SFA and PUFA and increased ω6‐ and ω3‐PUFA. Maternal height was associated with increased SFA and PUFA in Kolkata (1% increase per 1 cm), but body mass index showed no independent association with either ratio in either cohort. In summary, the socioeconomic factors of maternal education and household prosperity were associated with breast milk composition, although prosperity may only be important in higher cost of living communities. Associated maternal biological factors were height and infant birth order, but not adiposity. Further study is needed to elucidate the underlying mechanisms of these effects.